Systematic Literature Review : Pendekatan Kurikulum Berbasis Cinta (KBC) Pada Kemampuan Komunikasi Matematis Siswa MTs - Elisha Farmah; Nurul Anriani; Novaliyosi Novaliyosi (Jurnal Penelitian dan Pembelajaran Matematika, 2026)
This study examines the implementation of Independent Learning with the Love-Based Curriculum (KBC) approach on the mathematical communication skills of Madrasah Tsanawiyah students. Indonesian students' mathematical communication skills are still low based on the results of PISA and TIMSS, especially in working on narrative-shaped problems with everyday contexts. The Systematic Literature Review method was used to analyze 30 journals from Google Scholar for the 2020-2025 period that discuss the implementation of mathematics learning, mathematical communication skills, and innovative learning approaches. Data were analyzed using a qualitative descriptive approach with thematic categorization and narrative synthesis techniques. The results of the study indicate that the integration of KBC with the Independent Curriculum through differentiated learning on the Independent path has a positive effect on students' mathematical communication skills in the aspects of visual representation, written expression, and the use of mathematical symbols.